Method of selection technology of restoration of monuments of architecture - Osypov, S. (Ways to Improve Construction Efficiency, 2015)
The article discusses the technique of choice of technology of restoration of monuments of architecture, which builds on the systemic approach, focused synthesis of possible methods (depending on the type of restoration, etc.), the use of technological and design solutions restoration with scientific and feasibility study, the use of multi-criteria methods and technological feasibility study of rational choices.